Effect of Drying Temperature and Slice Thickness on Drying Kinetics, Moisture Diffusivity, Energy Use, and Color Change in Convectively Dried Chayote Squash Slices - Nurkhoeriyati, Tina; Rustandi, Ignatius Arya Krishna; Mwape, Mwewa Chikonkolo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Insufficient fiber intake is strongly associated with chronic diseases. Chayote squash (Sechium edule), widely available in Indonesia, has potential as a fiber source, and drying provides a practical method for its use in food products. This study evaluated the drying kinetics, specific energy consumption (SEC), total color change (ΔE*ab), and effective moisture diffusivity (Deff) of chayote slices under different temperatures (50, 60, and 70 °C) and thicknesses (3 and 6 mm) to determine the optimum drying conditions. Drying time (DT) ranged from 150 min (70 °C, 3 mm) to 350 min (50 °C, 6 mm). The approximation of diffusion and the Midilli and others models best represented the drying kinetics. The highest SEC was 3.40×10⁶ kJ·kg⁻¹ (60 °C, 3 mm), while other treatments showed no significant differences. Deff increased with temperature and thickness (3.38×10⁻¹⁰ to 1.28×10⁻⁹ m²·s⁻¹). Food color, an important factor influencing consumer acceptance, showed no significant ΔE*ab differences across treatments. The optimum drying condition determined was 70 °C with 3 mm slices (DT of 149 min, ΔE*ab of 16.62, SEC of 3.02×10⁶ kJ·kg⁻¹). These findings provide insights into designing chayote drying processes that achieve desirable quality while minimizing energy consumption.